VILLAGE DEVELOPMENT BASED ON COMMUNITY PARTICIPATION IN SUKANAGARA VILLAGE - Rizki Putri Purnama; Cecep Cahya Supena; Eet Saeful Hidayat (JGSRD: Journal of Government Science and Rural Development, 2022)
The level of community participation in village development activities is still quite low, especially in Sukanagara Village, Lakbok District, Ciamis Regency. This is evidenced by the lack of community participation in several development programs that are prioritized by the Sukanagara Village Government. The method used is a qualitative method, with data analysis techniques with triangulation of interviews, documentation, and literature studies. The results showed that the level of community participation was quite good, which was indicated by the existence of obstacles in development activities in the village. These obstacles include: (1) the lack of community willingness to spend their time to assist the implementation of development, starting to reduce the sense of cooperation in the community; (2) not yet optimal donation of funds for the procurement of materials; and (3) lack of public awareness and concern to participate in maintaining development.